2006
DOI: 10.1016/j.lmot.2005.06.004
|View full text |Cite
|
Sign up to set email alerts
|

The effects of physical context changes and multiple extinction contexts on two forms of renewal in a conditioned suppression task with humans

Abstract: The effects of 1 Running head: RENEWAL OF CONDITIONED SUPPRESSION IN HUMANS The effects of physical context changes and multiple extinction contexts on two forms of renewal in a conditioned suppression task with humans

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
51
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(60 citation statements)
references
References 32 publications
8
51
0
1
Order By: Relevance
“…Our finding that extinction in multiple contexts reduced ABC renewal is consistent with previous evidence (e.g., Bouton et al, 2006a, b;Glautier et al, 2013;Gunther et al, 1998;Neumann, 2006;Vansteenwegen et al, 2007; but see Bouton et al, 2006a), and the present study demonstrates the generality of the previous work. In the case of ABA renewal, however, the evidence is less clear.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Our finding that extinction in multiple contexts reduced ABC renewal is consistent with previous evidence (e.g., Bouton et al, 2006a, b;Glautier et al, 2013;Gunther et al, 1998;Neumann, 2006;Vansteenwegen et al, 2007; but see Bouton et al, 2006a), and the present study demonstrates the generality of the previous work. In the case of ABA renewal, however, the evidence is less clear.…”
Section: Discussionsupporting
confidence: 93%
“…In accordance with the present study, other researchers have also reported no attenuation of ABA renewal due to extinction in multiple contexts (e.g., Betancourt et al, 2008;Bouton et al, 2006a;Neumann et al, 2007). However, there have also been a number of demonstrations of the effectiveness of extinction in multiple contexts in ABA renewal (e.g., Chelonis et al, 1999;Neumann, 2006). Some factors might explain these differences.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…For example, auditory stimuli can be used as CS while changes in the screen color of a monitor provide the conditioning context (Armony and Dolan 2001). Context changes can also be implemented by modifying ambient lighting conditions and/or by playing different background noises (Effting and Kindt 2007;Neumann et al 2007;Neumann 2006;Vansteenwegen et al 2005). It is unclear how these studies relate to animal investigations.…”
Section: Context Conditioningmentioning
confidence: 99%